Penyusunan Ensiklopedia Berbasis Keragaman Burung Lokal - Endang Tri Handayani; Nurul Kusuma Dewi; Cicilia Novi Primiani (Universitas Sebelas Maret, 2021)
Learning media in the form of books or prints are increasingly being marginalized by more modern and sophisticated learning media. Therefore, it is important to compile an encyclopedia that is packaged practically. The high biodiversity in Indonesia can support the preparation of an encyclopedia. The purpose of compiling this encyclopedia is to find out the diversity of local birds. The preparation of the encyclopedia begins with analyzing the encyclopedia, designing the encyclopedia, and validating the encyclopedia. The results of the encyclopedia validation show that it is feasible to use with a material percentage of 75% and 91.67% media.